Artesunate Reduces Remifentanil-induced Hyperalgesia and Peroxiredoxin-3 Hyperacetylation via Modulating Spinal Metabotropic Glutamate Receptor 5 in Rats. (1st April 2022) - Zhang, Linlin; Zhao, Yuying; Gao, Tianyu; Zhang, Haoyue; Li, Jing; Wang, Guolin; Wang, Chunyan; Li, Yize
Highlights: Remifentanil induces mGluR5-dependent peroxiredoxin-3 hyperacetylation. Artesunate reduces remifentanil-induced hyperalgesia and mGluR5 expression. Artesunate reduces remifentanil-induced peroxiredoxin-3 hyperacetylation. mGluR5 antagonist prevents remifentanil-induced hyperalgesia. Artesunate impairs the mGluR5 agonist-evoked acute pain. Abstract: The experimental investigations on the pathogenesis of remifentanil-induced hyperalgesia (RIH) have been primarily conducted, but the effective treatment of RIH remains unclear. Recent reports highlight the necessity of ionotropic glutamate receptors in oxidative damage in spinal nociceptive transduction. Artesunate, the 1st-line anti-malaria drug, has been identified to be valid in removing superoxide in several pathological conditions. This study evaluated whether artesunate inhibits RIH via regulating metabotropic glutamate receptor 5 (mGluR5) and mitochondrial antioxidant enzyme peroxiredoxin-3 in rats. Artesunate was injected intrathecally 10 min before intravenous infusion of remifentanil (1 μg·kg −1 ·min −1 for 60 min) in rats. The antinociception of artesunate was verified by assessment of paw withdrawal mechanical threshold and paw withdrawal thermal latency. Spinal mGluR5 expression and peroxiredoxin-3 hyperacetylation were examined. Also, both the mGluR5 agonist DHPG and antagonist MPEP were utilized to explore the involvement of mGluR5 in the anti-hyperalgesic property of artesunate. Here, we found that artesunate (10 μg and 100 μg but not 1 μg) prevented RIH in a dose-dependent manner. Artesunate reduced remifentanil-related spinal over-expression of mGluR5 gene and protein, and hyperacetylation of peroxiredoxin-3. Intrathecal application of MPEP (10 nmol and 100 nmol but not 1 nmol) inhibited behavioral RIH and peroxiredoxin-3 acetylation. Moreover, hyperalgesia and peroxiredoxin-3 hyperacetylation were attenuated after the combination of artesunate (1 μg) and MPEP (1 nmol). Additionally, artesunate treatment reversed acute pain and peroxiredoxin-3 hyperacetylation following spinal exposure to DHPG. In conclusion, intrathecal injection of artesunate impairs RIH by down-regulating spinal mGluR5 expression and peroxiredoxin-3 hyperacetylation-mediated oxidative stress in rats.